2018
DOI: 10.5380/rsa.v19i1.51511
|View full text |Cite
|
Sign up to set email alerts
|

Influência De Diferentes Fontes De Matéria Orgânica Em Componentes Fisiológicos De Folhas Da Espécie Schinus Terebinthifolius Raddi. (Anacardiaceae)

Abstract: O objetivo deste trabalho foi avaliar o efeito das diferentes fontes de matéria orgânica incorporadas ao substrato sobre os índices fisiológicos e metabólitos secundários. O experimento foi conduzido no IFES Campus Itapina em um delineamento de blocos casualizados, e os tratamentos consistiram de cinco fontes alternativas de matéria orgânica na proporção de 20% misturadas ao substrato de terra pura. Foram avaliados os teores de clorofilas a, b, total, carotenoides e suas relações através da extração de clorofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A study on the development of Brazilian peppertree under different residues as substrate source showed changes in chlorophyll b contents when dairy residues and urban compost were used in the substrate (Sales et al, 2018). However, these same authors found no changes in chlorophyll a and total chlorophyll contents.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…A study on the development of Brazilian peppertree under different residues as substrate source showed changes in chlorophyll b contents when dairy residues and urban compost were used in the substrate (Sales et al, 2018). However, these same authors found no changes in chlorophyll a and total chlorophyll contents.…”
Section: Resultsmentioning
confidence: 95%
“…The use of biochar has been reported in some crops: in papaya associated with microorganisms (Matos et al, 2018), in rapeseed associated with mineral fertilizers (Tian et al, 2021) and in Brazilian peppertree (Sales et al, 2018). This residue supplies nutrients to plants and can increase their performance, increase the contents of total chlorophyll, chlorophyll a and chlorophyll b, as well as improving the chemical attributes of the soil (Matos et al, 2018;Sales et al, 2018;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaf area is a fundamental component for plants, since the larger is the leaf area, the greater the light uptake by the plant and the greater the production of metabolic energy, which will be responsible for the maintenance of plant metabolism and growth, as well as in determining the productivity of the plant (Koester et al, 2014;Sales et al, 2017). Sales et al (2018c) studying chlorophyll content in Schinus terebinthifolius Raddi seedlings cultivated in different substrates, showed that the addition of tannery sludge in the substrate positively favors chlorophyll content, as well as other organic materials added in other compounds. The higher organic matter content and nutrients of these substrates may result in higher chlorophyll production and cellular structures, resulting in a larger leaf area (Sales et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The use of organic residues in agriculture has increasingly aroused the attention of researchers and led to increased efforts to demonstrate their effects on several species of interest, with the objective of reducing the environmental impact generated by the disposal of these materials (Restrepo et al, 2013;Sales et al, 2017). There is a strong potential for the use of industrial residues, which are strongly correlated with the growth and physiology of agricultural plants, as observed by Oberpaur et al (2012), Sales et al (2018a), Berilli et al (2018a) and Quartezani et al (2018).…”
Section: Introductionmentioning
confidence: 99%